INDEPENDENSI KEJAKSAAN DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA TELAAH KRITIS TERHADAP UNDANG-UNDANG NOMOR 16 TAHUN 2004 TENTANG KEJAKSAAN REPUBLIK INDONESIA - Dedi Sahputra; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Speaking about the state of law then the consequences of all activities required to lean administration and based on the rule of law. One of the important principles of rule of law is the guarantee of the implementation of independent judicial power, free from the influence of other powers to organize judiciary to enforce the law and justice. In the Constitution of the Republic of Indonesia Year 1945 before the change and after the change are not set explicitly (explicit) about the presence of the Prosecutor of the Republic of Indonesia, but only implied (implicit) in Article 24 paragraph 3 provides that: